2016
DOI: 10.1002/adma.201602997
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Polymer Metal–Organic Framework Hybrids for Effective Photothermal Therapy of Colon Cancers

Abstract: A UiO-66 core with various sizes acts as heterogeneous nucleation center and enables aniline polymerization under ambient conditions. The as-synthesized UiO-66@PAN possesses uniform size and excellent dispersibility in aqueous solution. UiO-66@PAN can be internalized by cancer cells via endocytosis, and indicates significant photothermal therapeutic effect in vitro, and can effectively inhibit the growth of colon cancers in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(116 citation statements)
references
References 66 publications
(21 reference statements)
3
109
0
1
Order By: Relevance
“…Our own results show improved stability, drug release, and cell-uptake properties with biocompatible PEG chains, and recent work has shown that polyaniline-modified UiO-66 is effective and safe for anticancer photothermal therapy 100 . We expect the versatility of the click modulation protocol to allow a variety of MOFs to be selectively surface functionalized with a variety of chemical units and have immediate application not only in biomedical settings but also in selective adsorption and separation processes and catalysis.…”
Section: Resultsmentioning
confidence: 64%
“…Our own results show improved stability, drug release, and cell-uptake properties with biocompatible PEG chains, and recent work has shown that polyaniline-modified UiO-66 is effective and safe for anticancer photothermal therapy 100 . We expect the versatility of the click modulation protocol to allow a variety of MOFs to be selectively surface functionalized with a variety of chemical units and have immediate application not only in biomedical settings but also in selective adsorption and separation processes and catalysis.…”
Section: Resultsmentioning
confidence: 64%
“…Regarding cellular assays, coated NPs did not induce any cytotoxicity in both murine colon cancer CT26 and human colon cancer HTC116 cell lines, but once irradiated, nearly 70% cells were dead. In vivo tests carried out with both UiO‐66@PAN and NIR irradiation showed a complete tumor regression after 10 d, when compared to the controls (untreated or NPs alone), proving that UiO‐66@PAN was a good candidate for PTT‐based cancer therapy …”
Section: Surface Modifications Of Nanomofsmentioning
confidence: 89%
“…Numerous strategies have been proposed so far to modify the surface of nanoMOFs using a large variety of molecules, such as nucleic acids, polymers, cyclodextrins (CDs), or lipids, resulting into various degrees of improvement of the particles properties. One can classify these approaches into three categories: covalent, noncovalent, ( Table 2 ) or core–shell, as detailed below.…”
Section: Surface Modifications Of Nanomofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie and co‐workers combined the zirconium‐based nanoscale MOFs (UiO‐66) and 808 nm NIR‐absorbing polymer (PAN) to construct a UiO‐66@PAN nanocomposite with good photostability, excellent NIR absorbance and outstanding photothermal activity for PTT. The results showed that tumors treated with UiO‐66@PAN+NIR looked like complete regression compared to the control group or the group treated with UiO‐66@PAN, furthermore, the tumor suppression rate was calculated to be about 93% …”
Section: Tumor Therapymentioning
confidence: 99%